Conceiving Selves and Others: Sterne and Croatian Culture - Jukić, Tatjana (Array, 2004)
The text analyzes the Croatian reception of Laurence Sterne, specifically the Croatian Sterne of the nineteenth and early twentieth centuries as the Sterne of travelogue and its extreme generic borderliness, and the post-Second-World-War Croatian Sterne as the Sterne of literary theory, with the implication that both these Sternes remain stakes in the difficult cultural politics embracing the hyperactivity of Others and Othering.